2014
DOI: 10.1039/c4ta00940a
|View full text |Cite
|
Sign up to set email alerts
|

Binder-free rice husk-based silicon–graphene composite as energy efficient Li-ion battery anodes

Abstract: In this study, an energy efficient Li-ion battery anode composite system based on silicon nanoparticles and graphene has been demonstrated, wherein the raw materials were obtained from waste by-products such as rice husk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 38 publications
3
65
0
2
Order By: Relevance
“…[ 127 ] Synthesized Si nanoparticles : a) Magnesiothermic reduction: The magnesiothermic reduction process is a common method for producing Si from silicon dioxide. [ 128 ] CAG/Si@ SiOx composites produced via magnesiothemic reduction of mesoporous SiO 2 , exhibiting a reversible capacity of 763 mAh g −1 at 100 mA g −1 after 50 cycles, were reported by Tao et al [ 129 ] A comparable outcome was observed by Wong et al [ 130 ] who developed a composite paper composed of graphene and rice husk-based Si NPs via magnesiothermic reduction process. It afforded a capacity of ≈650 mAh g −1 at 1 A g −1 after 30 cycles.…”
Section: Reviewsupporting
confidence: 71%
See 1 more Smart Citation
“…[ 127 ] Synthesized Si nanoparticles : a) Magnesiothermic reduction: The magnesiothermic reduction process is a common method for producing Si from silicon dioxide. [ 128 ] CAG/Si@ SiOx composites produced via magnesiothemic reduction of mesoporous SiO 2 , exhibiting a reversible capacity of 763 mAh g −1 at 100 mA g −1 after 50 cycles, were reported by Tao et al [ 129 ] A comparable outcome was observed by Wong et al [ 130 ] who developed a composite paper composed of graphene and rice husk-based Si NPs via magnesiothermic reduction process. It afforded a capacity of ≈650 mAh g −1 at 1 A g −1 after 30 cycles.…”
Section: Reviewsupporting
confidence: 71%
“…Si/graphite@graphene spray-drying/heat treatment 100 803.3 62.2% ( n = 50) [121] Si NPs/graphene sheets freeze-drying/thermal reduction 100 1271 67% ( n = 100) [122] Graphene wrapped Si freeze-drying method 100 1248.8 78.8% ( n = 100) [123] Grafted Si NPs/graphene freeze-drying method 2000 1184 76% ( n = 300) [109] Si from magnesiothermic reduction 3D Si/graphene sol-gel followed by reduction 5000 530 68% ( n = 100) [131] Porous Si@SiO x / graphene chemical activation/reduction 100 831 91.8% ( n = 50) [129] Si NPs/graphene ball milling/thermal treatment 400 1314 31.2% ( n = 50) [133] RH-Si NPs/graphene precipitation/reduction 1000 1000 75% ( n = 30) [130] Graphene/Si-C nanocomposite vacuum fi ltration followed by reduction 400 1100 99% ( n = 100) [132] Si from CVD and others…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…The production of silica nanoparticles is anticipated to be non-toxic and economic in nature. An investigation on forming amorphous silica nanoparticles from rice husk (RH) biomass is studied for different applications (Kalapathy et al 2000;Carmona et al 2013;Wong et al 2014). However, finding the lucrative resources for large scale production of silica nanoparticles is still need to be refined as RH is also useful in animal feeds.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, significant efforts have been devoted to the application of rice husk in many fields such as fuel production [18][19][20], fertilizers [21], construction materials [22], catalytic supports [23], and capacitors [24], etc. More recently, however, Wong et al [25] and Wang et al [26] employed rice husk as a raw material for lithium ion battery-related applications. Thus, how to efficiently utilize rice husk is still an interesting topic.…”
Section: Introductionmentioning
confidence: 98%